2023
DOI: 10.1073/pnas.2303523120
|View full text |Cite
|
Sign up to set email alerts
|

Distinct context- and content-dependent population codes in superior colliculus during sensation and action

Eve C. Ayar,
Michelle R. Heusser,
Clara Bourrelly
et al.

Abstract: Sensorimotor transformation is the process of first sensing an object in the environment and then producing a movement in response to that stimulus. For visually guided saccades, neurons in the superior colliculus (SC) emit a burst of spikes to register the appearance of stimulus, and many of the same neurons discharge another burst to initiate the eye movement. We investigated whether the neural signatures of sensation and action in SC depend on context. Spiking activity along the dorsoventral axis was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Recently, there has been increased interest in comparing SU and MU activity in both animals and humans (Ayar et al, 2023;Ahmadi et al, 2021;Burns et al, 2010;Christie et al, 2015;Drebitz et al, 2019;Gilja et al, 2015;Pandarinath et al, 2017;Trautmann et al, 2019). For example, Trautmann and colleagues (Trautmann et al, 2019) suggested that MU recordings provide both the practical benefit eliminating spike sorting (required for SU analysis) and reducing the dimensionality of the signal without losing important information content.…”
Section: Multi-unit Vs Single-unit Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, there has been increased interest in comparing SU and MU activity in both animals and humans (Ayar et al, 2023;Ahmadi et al, 2021;Burns et al, 2010;Christie et al, 2015;Drebitz et al, 2019;Gilja et al, 2015;Pandarinath et al, 2017;Trautmann et al, 2019). For example, Trautmann and colleagues (Trautmann et al, 2019) suggested that MU recordings provide both the practical benefit eliminating spike sorting (required for SU analysis) and reducing the dimensionality of the signal without losing important information content.…”
Section: Multi-unit Vs Single-unit Activitymentioning
confidence: 99%
“…Further, whereas the spatiotemporal progression of the SU data showed various dips and rises during the delay period, perhaps related to microsaccades (Heusser et al, 2022), the MU data showed a 'smoother' transition, suggesting a more robust sensorimotor signature. Considering the relative ease of recording online MU activity (without the need for offline spike sorting), this suggests that MU activity could be sufficient for certain practical applications requiring low-dimensional information (Ayar et al, 2023;Trautmann et al, 2019). For example, MU activity could be observed to rapidly assess the health of sensorimotor transformations during presurgical recordings in patient populations.…”
Section: Implications For Sensorimotor Controlmentioning
confidence: 99%
See 3 more Smart Citations